Assessment of the diagnostic accuracy of nerve conduction study and the correlation between severity of symptoms and nerve conduction studies in carpal tunnel syndrome - Alex, Benjamin; Kattoor, Mithun Joy; Edayalamuriyil, Samson Samuel (International Journal of Research in Orthopaedics, 2019)
Background: This study was done to assess the diagnostic accuracy of nerve conduction study in carpal tunnel syndrome and comparability of nerve conduction measures before and after carpal tunnel release. Methods: 31 patients (30 females and 1 male) with carpal tunnel syndrome were subjected to nerve conduction study and Boston symptom severity scores before surgery and at 3 months post-operative period and nerve conduction values compared. The effect of duration of symptoms on nerve conduction values was studied. Results: Nerve conduction studies were found to be reliable in diagnosing carpal tunnel syndrome. 61.30% patients showed a right-handed involvement, or right side getting affected first in a bilateral case. 60-80% patients had Boston symptom severity scores which were comparable to the nerve conduction grades ascertaining the relationship between them. Only 58.8% patients with extreme and severe NCS grades preoperatively showed improvement post-surgical release. In patients with symptoms for more than 12 months, only 33.33% had improved nerve conduction grades post-surgical release at 3 months, validating the need for early surgical release. Conclusions: Nerve conduction study was found to be a reliable diagnostic modality for diagnosis of carpal tunnel syndrome and nerve conduction study values correlated with the Boston symptom severity score. The post-operative nerve conduction values revealed definite neurological improvement in patients who underwent early surgical management. Hence, we recommend early release for carpal tunnel syndrome patients for speedy recovery from the condition.